Intensification of degradation of methomyl (carbamate group pesticide) by using the combination of ultrasonic cavitation and process intensifying additives - Raut-Jadhav, Sunita; Pinjari, Dipak V.; Saini, Daulat R.; Sonawane, Shirish H.; Pandit, Aniruddha B. (Ultrasonics Sonochemistry, 2016)
In the present work, the degradation of methomyl has been carried out by using the ultrasound cavitation (US) and its combination with H2O2, Fenton and photo-Fenton process. The study of effect of operating pH and ultrasound power density has indicated that maximum extent of degradation of 28.57% could be obtained at the optimal pH of 2.5 and power density of 0.155 W/mL. Application of US in combination with H2O2, Fenton and photo-Fenton process has further accelerated the rate of degradation of methomyl with complete degradation of methomyl in 27 min, 18 min and 9 min respectively. Mineralization study has proved that a combination of US and photo -Fenton process is the most effective process with maximum extent of mineralization of 78.8%. Comparison of energy efficiency and cost effectiveness of various processes has indicated that the electrical cost of 79892.34 Rs./m(3) for ultrasonic degradation of methomyl has drastically reduced to 2277.00 Rs./m(3), 1518.00 Rs./m(3) and 807.58 Rs./m(3) by using US in combination with H2O2, Fenton and photo-Fenton process respectively. The cost analysis has also indicated that the combination of US and photo-Fenton process is the most energy efficient and cost effective process. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fenton; Hydrogen peroxide; Methomyl; Photo-Fenton; Synergistic coefficient; Ultrasound cavitation

Treatment of the pesticide industry effluent using hydrodynamic cavitation and its combination with process intensifying additives (H2O2 and ozone) - Raut-Jadhav, Sunita; Badve, Mandar P.; Pinjari, Dipak V.; Saini, Daulat R.; Sonawane, Shirish H.; Pandit, Aniruddha B. (Chemical Engineering Journal, 2016)
Hydrodynamic cavitation (HC) and its combination with H2O2 and ozone have been applied in the present work for the treatment of industrial pesticide effluent. Initially, the effect of dilution of the effluent on the efficacy of hydrodynamic cavitation has been studied using circular venturi as a cavitator. Although an increase in the extent of dilution has not shown any beneficial effect on the actual moles of pollutant degraded, hybrid processes have been studied using 1:5 dilution due to very high TDS content of the effluent. Treatment of the industrial pesticide effluent using HC + ozone (3 gbh) process has demonstrated that the biodegradability index (BI) of the effluent increases from 0.123 to 0.324 after 2 h of operation. The rate of COD and TOC reduction has also increased by many folds by using HC in combination with ozone. In addition this, the treatment of industrial pesticide effluent using HC + H2O2 has also indicated that the rate of COD and TOC reduction increases significantly by using HC in combination with various loadings of H2O2. The study of interference of added H2O2 on the COD analysis has exhibited that the COD equivalence is 0.441 mg/L for 1 mg/L of H2O2. The energy efficiency and operating cost of various hybrid processes have been compared based on the cavitational yield and the cost of electricity. The combined process of HC and H2O2 has observed to be the most cost-effective one due to its higher cavitational yield and lower power consumption. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biodegradability index; Hydrodynamic cavitation; Hydrogen peroxide; Industrial pesticide effluent; Ozone; Venturi

Synthesis of copper nanoparticles in presence of surfactants and evaluation of heat transfer performance of copper nanofluid - Kapadnis, Chetan V.; Gundeli, Kartik P.; Saini, Daulat R.; Bhatkhande, Dhananjay S. (Journal of Nanofluids, 2017)
Copper nanoparticles were synthesized by reduction of copper nitrate hexahydrate using glucose as a green reducing agent. Effect of various synthesis parameters such as the amount of reducing agent, type of surfactant, the concentration of surfactant on particle size and morphology has been studied. Particles thus synthesized were characterized using analytical tools like X-ray Diffraction (XRD), Dynamic Light Scattering (DLS) and Scanning Electron Microscopy (SEM). XRD results show copper peaks at 2 angles 43.34, 50.48 and 74.19° corresponding to the planes (111), (200) and (220) respectively and possessing FCC (Face Centred Cubic) crystal lattice and polydispersed particles with crystallite size ranging from 43 to 103 nm. Further Cu nanoparticles were dispersed in water to prepare nanofluid and heat transfer properties such as heat transfer coefficient, viscosity and density were evaluated. Nanofluid models proposed elsewhere were also used for theoretical property evaluations. Nearly 100% increase in heat transfer coefficient was observed at 1% (by volume) particle concentration of copper nanoparticles in water.
Keywords: Chemical Reduction; Copper nanoparticles; green synthesis; Nanofluids; surfactant